2018
DOI: 10.2298/pac1804374t
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous TiO2 spheres as a photoanodic material in dye-sensitized solar cells

Abstract: Mesoporous TiO 2 films with spherical architectures and promising performance in dye-sensitized solar cells (DSSCs) were prepared. The morphology of the films was investigated by scanning electron microscopy. Transmission electron microscopy analysis of the spheres disclosed the elongated shape of sub-20 nm primary particles, while BET analysis revealed their high surface area of 135 m 2 /g. Anatase presence was observed in the films based on X-ray diffractometry, selected-area electron diffraction analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The smaller R ct suggests better interaction with the electrolyte, which would support enhanced photocatalytic activity for benzylic alcohol oxidation at photoanode. The electron lifetimes (τ n ) of FTO|t-TiO 2 |RuC films were calculated using eq : , where f max is the frequency at which the phase angle reaches the maximum in the bode plots of the EIS test (Figure S6). The maximum frequencies of for FTO|t-TiO 2 |RuC films and the derived electron lifetimes are summarized in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller R ct suggests better interaction with the electrolyte, which would support enhanced photocatalytic activity for benzylic alcohol oxidation at photoanode. The electron lifetimes (τ n ) of FTO|t-TiO 2 |RuC films were calculated using eq : , where f max is the frequency at which the phase angle reaches the maximum in the bode plots of the EIS test (Figure S6). The maximum frequencies of for FTO|t-TiO 2 |RuC films and the derived electron lifetimes are summarized in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the fill factor (FF) values registered for all devices are very high (>70%), which indicates that the semiconductor manufacturing process developed by our research group ensures high-quality cells. Fill factor is a crucial DSSC parameter and represents, among others, the energy loss caused by series resistance, electrolyte thickness (spacer influence), and counter electrode production quality (Pt layer) [ 88 , 89 , 90 ]. It may be observed that indeed the TCO resistance (R 1 ) correlates with FF since the highest FF value was observed for DSSC with the lowest R 1 values (see Table 7 ).…”
Section: Resultsmentioning
confidence: 99%